Pendekatan Diagnosis dan Tata Laksana Multipel Sklerosis - Sutanto, Anyelir; Widya Andini, Putri; Maharani, Kartika; Imran, Darma; estiasari, riwanti (PERDOSNI, 2023)
We reported three cases of young adults with typical and atypical neurological manifestations, supported by positive brain and spinal imaging findings, along with cerebrospinal fluid (CSF) analysis consistent with McDonald's criteria 2017 for multiple sclerosis (MS). Clinical manifestations varied with optic neuritis, myelopathy, vertigo, ataxia, and urinating problems in relapsing-remitting patterns in two cases and progressive in one other. Brain MRI showed T2-hyperintense lesion in cortical/juxtacortical, periventricular, and infratentorial areas, coupled with a spinal cord lesion shown in spinal MRI. The CSF analysis for oligoclonal band type II was positive in all cases. All three patients received relapse therapy with post-therapy clinical improvement, followed by long-term therapy with DMD (disease-modifying drugs) fingolimod, interferon ÃŽÂ²-1a, and one patient was treated with mycophenolate mofetil. Careful clinical observation was maintained to evaluate different relapse rates.